2020
DOI: 10.1177/1177932220977490
|View full text |Cite
|
Sign up to set email alerts
|

An in silico Study of Two Transcription Factors Controlling Diazotrophic Fates of the Azolla Major Cyanobiont Trichormus azollae

Abstract: The cyanobiont Trichormus azollae lives symbiotically within fronds of the genus Azolla, and assimilates atmospheric nitrogen upon N-limitation, which earmarks this symbiosis to be a valuable biofertilizer in rice cultivation, among many other benefits that also include carbon sequestration. Therefore, studying the regulation of nitrogen fixation in Trichormus azollae is of great importance and benefit, especially the two topmost rungs of regulation, the NtcA and HetR transcription factors that are able to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In terms of Sphaerospermopsis abundance in S. monoica's crust, Cyanobacteria from Sphaerospermopsis BCCUSP55 genus could be related to nitrogen fixation at the soil surface. Sphaerospermopsis genus was previously reported to be closely related to a well-known nitrogen-fixing cyanobiont bacteria known as Nostoc (Gunawardana, 2020). This can be supported by the fact that at the family level, Nostocaceae cyanobacteria were abundant in S. monoica-associated samples, especially S. monoica's crust, while Balneolaceae was abundant in Sr. Another species, Sphaerospermopsis aphanizomenoides, was reported to not only grow faster than other Nostocales families in high temperature but also to be correlated with phytoplankton (Budzyńska et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…In terms of Sphaerospermopsis abundance in S. monoica's crust, Cyanobacteria from Sphaerospermopsis BCCUSP55 genus could be related to nitrogen fixation at the soil surface. Sphaerospermopsis genus was previously reported to be closely related to a well-known nitrogen-fixing cyanobiont bacteria known as Nostoc (Gunawardana, 2020). This can be supported by the fact that at the family level, Nostocaceae cyanobacteria were abundant in S. monoica-associated samples, especially S. monoica's crust, while Balneolaceae was abundant in Sr. Another species, Sphaerospermopsis aphanizomenoides, was reported to not only grow faster than other Nostocales families in high temperature but also to be correlated with phytoplankton (Budzyńska et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Serine is the most frequently found mutation and one of the most targeted destinations in relation to amino acids and consequently, is called a mutational hotspot [8]. is is primarily due to the two disjointed types of codons that are found in the genetic code that are encoding for the same amino acid, serene [9]. ey are as follows: UCN (UCA, UCC, UCG, and UCU) and AGY (AGU and AGC), which are farther apart than a single nucleotide substitution, which makes two distant groupings and six unique codons for serine (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…One key regulator of nitrogen fixation, heterocyst development and function, is the NtcA transcription factor, which is thought to regulate the downstream function of >2000 mostly nitrogen-metabolism-related genes [22]. We searched for the NtcA binding promoter region in the WP_013192178.1 encoding gene to see whether it was under top-down regulation.…”
Section: Promoter For the Ntca Transcription Factormentioning
confidence: 99%
“…Under nitrogen-rich conditions, 2-oxoglutarate counts are low and NtcA is found in an inactive form [22]. In a recent publication, it was shown that the NtcA transcription factor of T. azollae putatively uses a putative disulfide bond to perform its robust function in modifying gene expression using NtcA responsive promoters [22].…”
Section: Promoter For the Ntca Transcription Factormentioning
confidence: 99%
See 1 more Smart Citation